Global A-to-I RNA editing during myogenic differentiation of goat MuSCs - Xu, Xiaoli; Zhang, Mancheng; Zhan, Siyuan; Chen, Yuan; Wei, Chengqi; Cao, Jiaxue; Guo, Jiazhong; Dai, Dinghui; Wang, Linjie; Zhong, Tao; Zhang, Hongping; Li, Li (Frontiers in Veterinary Science, 2024)
BackgroundRNA editing, especially A-to-I editing sites, is a common RNA modification critical for stem cell differentiation, muscle development, and disease occurrence. Unveiling comprehensive RNA A-to-I editing events associated with myogenesis of the skeletal muscle satellite cells (MuSCs) is essential for extending our knowledge of the mechanism underpinning muscle development.ResultsA total of 9,632 RNA editing sites (RESs) were screened in the myoblasts (GM), myocytes (DM1), and myotubes (DM5) samples. Among these sites, 4,559 A-to-I edits were classified and further analyzed. There were 3,266 A-to-I sites in the protein-coding region, out of which 113 missense sites recoded protein. Notably, five A-to-I sites in the 3′ UTR of four genes (TRAF6, NALF1, SLC38A1, ENSCHIG00000019092) altered their targeted miRNAs. Furthermore, a total of 370 A-to-I sites with different editing levels were detected, including FBN1, MYH10, GSK3B, CSNK1D, and PRKACB genes. These genes were predominantly enriched in the cytoskeleton in muscle cells, the hippo signaling pathway, and the tight junction. Furthermore, we identified 14 hub genes (TUFM, GSK3B, JAK2, RPSA, YARS1, CDH2, PRKACB, RUNX1, NOTCH2, CDC23, VCP, FBN1, RARS1, MEF2C) that potentially related to muscle development. Additionally, 123 stage-specific A-to-I editing sites were identified, with 43 sites in GM, 25 in DM1, and 55 in DM5 samples. These stage-specific edited genes significantly enriched essential biological pathways, including the cell cycle, oocyte meiosis, motor proteins, and hedgehog signaling pathway.ConclusionWe systematically identified the RNA editing events in proliferating and differentiating goat MuSCs, which was crucial for expanding our understanding of the regulatory mechanisms of muscle development.